Improving Student's Quality in English Translation by Using Oblique Translation Method in PIQ Hidayatul Qur'an Wonosobo - Yusfiana, Ulya (DAS Institute, 2024)
The students are unfamiliar with the translation method, so the quality of their translation still needs to improve. It impacts the need for more messages convey in the English text they translate. The method of oblique translation is examined in this thesis. It attempts to establish the effectiveness of the Oblique Translation Method in raising the caliber of the English translations produced by the MTs Negeri 2 Wonosobo students who study in the PIQ Hidayatul Qur'an. The research methodology is a qualitative method, which is written by descriptive analysis. This study compares translation outcomes from the source language to the target language in the analysis units. The researcher uses the 8th and 9th grader students as the instrument of this research. In this research, the writer finds the result that shows the amount of data found in implementing the oblique translation method. The data is analyzed through a translation theory stated by Vinay and Darbelnet (1958). The researcher compared the experimental translation results (post-test and pre-test) also a few interviews from the object research. The sample in this study is MTs Negeri 2 Wonosobo students who lived at PIQ Hidayatul Qur'an Wonosobo. The data results of this study, with the score for the practical course (Oblique Translation Method) being 7.5, included in the category of moderately effective. The results show a difference between learning the Oblique Translation Method and without using it. Keywords: translation, student's translation quality, oblique translation method.